Exploring the impact of artificial sweeteners on diabetes management and glycemic control - Begum, Rukaiah Fatma; Nirenjen, S.; Rushendran, Rapuru; Manisha, M.; Pavithra, N.; Sridevi, S.; Singh, S. Ankul (Frontiers in Nutrition, 2025)
Diabetes mellitus (DM), a chronic metabolic disorder characterized by impaired glucose metabolism, has emerged as a significant global health challenge. Effective management of diabetes encompasses not only medical interventions but also lifestyle and dietary modifications. Artificial sweeteners (ASs), due to their low caloric content and minimal impact on blood glucose levels, offer promising potential as sugar substitutes for individuals aiming to manage glycemic control. Compounds such as aspartame, sucralose, and stevia mimic the sweetness of sugar without causing hyperglycemia, making them suitable for diabetic patients. This chapter explores the role of ASs in diabetes management, with a special focus on their mechanisms of action, including modulation of insulin sensitivity and glucose metabolism. An extensive review of preclinical and clinical studies evaluates the efficacy, safety, and long-term effects of ASs in glycemic control, highlighting their ability to reduce caloric intake, promote satiety, and support glycemic control and insulin sensitivity in individuals with diabetes. Emerging evidence suggests that ASs may influence gut microbiota, potentially affecting metabolic outcomes and insulin sensitivity, thus presenting opportunities for personalized interventions. Despite their benefits, awareness of potential risks, such as altered taste perception and over-reliance on ASs, is crucial. Integrating ASs within a broader lifestyle approach, comprising regular exercise and balanced nutrition, ensures optimal outcomes in diabetes management. This chapter emphasizes the importance of precision medicine in tailoring AS use to individual metabolic responses, underscoring its role as an adjunct to comprehensive diabetes care strategies.